Technical controversy in international standardization - Susanne K. Schmidt; Raymund Werle (Max-Planck-Institut für Gesellschaftsforschung, 1993)
The development of larger technical systems relies on the coordination of autonomous action of a multitude of individuals and organizations. Institutional settings, often neglected in the analysis of technical development, help to achieve such coordination. Our analysis of international technical standardization in telecommunications highlights an institutionalized process aiming at the creation of compatibility standards as the means for coordination. Formal procedural, membership, and decision rules combined with informal sets of expectations constitute the normative basis of the CCITT, the most prominent international standardization organization in telecommunications. Although scientific, political and economic aspects can be equally important for standards, the CCITT selectively legitimizes a technical perspective. Political and scientific reasoning is restricted, an open economic perspective even completely banned, unless they can be translated into a technical perspective. This increases the capacity to proceed on a consensusal basis and often facilitates reaching a con-sensus in a controversy. Standardization of Videotex and Telefax empirically examplifies this, and at the same time demonstrates the limits of pure technical reasoning to resolve genuine political or economic conflicts. – – Die Entwicklung großer technischer Systeme hängt von der Koordination autonomer Handlungen einer Vielzahl von Individuen und Organisationen ab. Institutionelle Arrangements, oft vernachlässigt in Analysen technischer Entwicklung, erleichtern dies. Unsere Analyse internationaler technischer Standardisierung in der Telekommunikation behandelt den Prozeß der Vereinbarung von Kompatibilitätsstandards, die Koordination ermöglichen. Formale Mitgliedschafts-, Entscheidungs- und Verfahrensregeln sowie informelle Erwartungsmuster bilden die normative Grundlage der Arbeit des CCITT, der wichtigsten internationalen Standardisierungsorganisation in der Telekommunikation. Obwohl wissenschaftliche, politische und ökonomische Aspekte gleich wichtig sein können für Standards, begünstigt der CCITT selektiv eine technische Perspektive. Politische und wissenschaftliche Argumentation ist nur eingeschränkt zulässig, eine offensichtlich ökonomische Sichtweise sogar völlig unzulässig, es sei denn eine Übersetzung in eine technische Perspektive gelingt. Dies verbessert die Möglichkeit, auf Konsensbasis zu arbeiten, und erleichtert oft die Einigung in Kontroversen. Die Standardisierung von Bildschirmtext und Telefax liefert hierfür empirische Beispiele und zeigt gleichzeitig die Grenzen rein technischer Argumentation auf, um politische oder ökonomische Konflikte zu lösen.
Keywords: 300